Performance Evaluation of Stone Mastic Asphalt and Hot Mix Asphalt Mixtures Containing Recycled Concrete Aggregate - Mohammad Saeed Pourtahmasb; Mohamed Rehan Karim (Advances in Materials Science and Engineering)
Environmental and economic considerations have encouraged civil engineers to find ways to reuse recycled materials in new constructions. The current paper presents an experimental research on the possibility of utilizing recycled concrete aggregates (RCA) in stone mastic asphalt (SMA) and hot mix asphalt (HMA) mixtures. Three categories of RCA in various percentages were mixed with virgin granite aggregates to produce SMA and HMA specimens. The obtained results indicated that, regardless of the RCA particular sizes, the use of RCA to replace virgin aggregates increased the needed binder content in the asphalt mixtures. Moreover, it was found that even though the volumetric and mechanical properties of the asphalt mixtures are highly affected by the sizes and percentages of the RCA but, based on the demands of the project and traffic volume, utilizing specific amounts of RCA in both types of mixtures could easily satisfy the standard requirements.